2019
DOI: 10.1186/s12974-019-1512-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in the NTS is associated with changes in cardiovascular reflexes during systemic inflammation

Abstract: Background Lipopolysaccharide (LPS)-induced systemic inflammation (SI) is associated with neuroinflammation in the brain, hypotension, tachycardia, and multiple organs dysfunctions. Considering that during SI these important cardiovascular and inflammatory changes take place, we measured the sensitivity of the cardiovascular reflexes baroreflex, chemoreflex, and Bezold-Jarisch that are key regulators of hemodynamic function. We also evaluated neuroinflammation in the nucleus tractus solitarius (NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 75 publications
7
43
2
1
Order By: Relevance
“…In the search for mechanisms underlying hemodynamic control during SI, we used spectral analysis of PI in the frequency domain, which showed that HF component of PI was significantly reduced at 3 hours after endotoxin in Control + LPS and in SAD + LPS in relation to Control + Sal (Fig 3 A and D). These observations are in line with the concept that LPS-induced tachycardia is triggered by mechanisms resulting in a decrease of vagal modulation to the heart (18). Significant changes in the autonomic control to the heart have been observed during the initial phase of sepsis-associated SI as a compensatory adjustment to avoid circulatory shock (29).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the search for mechanisms underlying hemodynamic control during SI, we used spectral analysis of PI in the frequency domain, which showed that HF component of PI was significantly reduced at 3 hours after endotoxin in Control + LPS and in SAD + LPS in relation to Control + Sal (Fig 3 A and D). These observations are in line with the concept that LPS-induced tachycardia is triggered by mechanisms resulting in a decrease of vagal modulation to the heart (18). Significant changes in the autonomic control to the heart have been observed during the initial phase of sepsis-associated SI as a compensatory adjustment to avoid circulatory shock (29).…”
Section: Discussionsupporting
confidence: 90%
“…Considering our previous study that documented hemodynamic and inflammatory changes 3 hours following LPS administration (18), cytokine levels were evaluated at this same period in plasma and spleen as an index of SI and the modulatory role of sino-aortic afferents on the splenic anti-inflammatory reflex, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The in situ expression of MTDH and the astrocytic marker GFAP was analyzed as described previously [27]. The fixed spinal cord was sectioned into 10 mm-thick slices, and probed with rabbit anti-MTDH (1:100, Proteintech), rabbit anti-GFAP (1:800, ServiceBio) and rabbit anti-DAPI (1:800, ServiceBio) primary antibodies, followed by Cy3-labeled goat anti-rabbit IgG secondary antibody (1:500, ServiceBio).…”
Section: Immunofluorescencementioning
confidence: 99%